NOMA-ALOHA With Prioritized Burst Repetition For Machine-Type Communications - Ramatryana, I Nyoman Apraz; Satrya, Gandeva Bayu; Budiman, Gelar; Mnaouer, Adel Ben (IEEE Transactions on Vehicular Technology, 2024)
This correspondence paper considers nonorthogonal multiple access (NOMA)-assisted slotted ALOHA (NOMA-ALOHA) for machine-type communications. NOMAALOHA is a hybrid ALOHA, where the transmitted information exploits NOMA in the physical layer and slotted ALOHA protocol in the medium access control (MAC) layer. In addition, a prioritized burst repetition (PBR) is proposed to improve the throughput of NOMA-ALOHA. The main idea is to reduce collision by exploiting burst repetition based on priority in MAC and iterative cancellation in the receivers. The asymptotic throughput is derived using density evolution, and the simulation results validate that PBR substantially improves the existing NOMA-ALOHA.
CRIS-Team Scopus Importer:2024-07-26
Keywords: burst repetition; Load modeling; machine-type communications; Media Access Protocol; NOMA; NOMA-ALOHA; priority; Protocols; Signal to noise ratio; Throughput; Uplink